Comparison of Saddle-Shaped Region of Head-Flow Curve between Axial-Flow Pump and Its Corresponding Axial-Flow Pump Device - Dongtao Ji; Weigang Lu; Linguang Lu; Lei Xu; Jun Liu; Wei Shi; Ye Zhu (Shock and Vibration)
In engineering, the highest operating head of the pumping station is usually controlled to be slightly lower than the lowest saddle bottom head of the axial-flow pump. However, in the practical operation, it is found that the highest operating head of the pumping station is obviously lower than the saddle bottom head of the pump device, which leads to the reduction of the operating range of the pumping station. To investigate the difference of lowest saddle bottom head between axial flow pump and axial flow pump device and apply it correctly, the energy performance tests of the TJ04-ZL-06 hydraulic model and its corresponding pump device were carried out to obtain the external curves, and numerical simulation was carried out to analyze and compare the internal flow field and pressure distribution. The results show that when the flow rate decreases, the first saddle-shaped region of the axial-flow pump and the saddle-shaped region of the pump device are caused by the decrease of the lift coefficient due to the increase of the attack angle between flow and blade. When the flow rate is less than 0.32Qd, the influence range of backflow in the inlet pipe is large, which leads to the high-pressure zone near the wall of the inlet pressure measurement section during the pump performance test, and hence the second saddle-shaped region of the axial-flow pump is essentially a measurement illusion. It is suggested that the inlet pressure measurement section should be set at least 4Dp away from the inlet flange of the impeller when testing the performance of the axial-flow pump under the condition of small flow rate, and the first saddle bottom head of the axial-flow pump or the saddle bottom head of the corresponding pump device can be considered as the control value of the highest head of the pumping station.